EFFECT OF IN OVO SUPPLEMENTATION OF HONEY IN FERTILE EGGS ON POST HATCH GROWTH PERFORMANCE OF BROILER CHICKENS - S. Abdullah; I. H Leghari; A. A. Moriani; N. Rajput; J. A. Gandhai; M. Nisa (Journal of Animal and Plant Sciences, 2018)
The present study was designed to evaluate the effects of in ovo supplementation of honey in fertile eggs on the post hatch growth performance of broiler chickens. In this regard, 120 fertile eggs were divided into 3 treatments and a control group. In ovo (20%) supplementation of honey at 0.5ml/egg was inoculated into yolk sac in each treatment group on day 15, 16 and 17 of incubation and the observations were made immediately after hatch, at the end of the brooding period and at the time of harvesting. The birds were observed for hatchability percentage and growth performance parameters. Our results showed no significant difference in the hatchability percentage (84 for non-injected control, 84, 90, 94% for honey injected on day 15,16 and 17 respectively) and hatchling weight (43.9,44.5,43.8 and 44.56g) among different groups. Similarly, heart weight (0.372, 0.362, 0.364 and 0.416g), intestinal weight ( 2, 2, 1.89 and 1.76g) and yolk weight ( 4.2,4.5, and 5.0g) were also non-significant among the groups. However, liver weight (1.31,1.34,1.06 and 1.13g; P< 0.0002) was significantly different among the different groups in day old chick. Day old chicken intestinal villi length (88.7, 83, 93 and 104 µm; P<0.0000) showed marked difference among the groups. th Moreover, treated groups at the end of the 14 day, also demonstrated no significant difference in the body weight, carcass weight and liver weight, however, intestinal villi length (392, 414, 429 and 469 (µm) ; P<0.0000) was significantly different among the groups. But at marketing stage, significant difference was observed among treated and control groups, in the average weight gain (1761g, 1735g, 1918g, and 1939g; P<0.0014), carcass weight (928, 890, 1010, and 1023g; P<0.0033) and gizzard weight (49.9, 46.5, 54.6, and 55g; P< 0.0007) . The feed efficiency values were significantly better in the honey inoculated groups than the non-treated group. It is concluded that in ovo supplementation of honey in fertile eggs can increase the size of visceral organs and improve post hatch growth performance of broiler chicks. Keys word: In ovo, honey, broiler, embryo, growth. development ( Uni et al., 2005) . Moreover, in ovo
Keywords: NA